Dramatic Character of Lermontov‘s Pechorin: The Medium of Creative Embodiment - H. Akhmedov, Ahmed; O. Khabibova, Tatyana; D. Yusupova, Patimat; M. Omarova, Siyanat; M. Rabadanova, Sabiyat; U. Pakhrutdinova , Ragimat (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the presented study is due to the lack of an adequate literary interpretation of the image of Pechorin, the main character of the novel by Mikhail Lermontov, who created one of the most hard-hitting works in the cultural history of Russia. The authors' proposed interpretation of Lermontov's Pechorin provides the reader with unbiased explanations of the essence of imagery, earlier related to the non-aesthetic perception of the creative image (socio-political, moral and ethical, etc.). The applied textual, comparative, and psychological methods allowed the following reasonable conclusion: the main value of Lermontov's novel lies in giving the reader an opportunity of aesthetic experiences in the form of empathy for the dramatic attitude of the protagonist to the world around. According to the authors, the drama of „A Hero of Our Time‟ novel is created by virtue of the two-sided depiction of the principal character: if the first side corresponds to the outer (event-driven) boundaries of his being, then the second (implicit) exposes the hero‟s modus operandi to extensive self-reflection; the principal character turns out wider and largely unsuited for the traditional boundaries and protests against them. The materials of the article are of practical value for successful teaching of literature as an art form on the secondary and university levels.